A prospective study examining the effects of treatment timing in the management of mandible fractures. Issue 9 (September 2018) - Hurrell, M.J.L.; David, M.C.; Batstone, M.D.
Abstract: The ideal timing for treatment of mandible fractures has not been well established. The objective of this study was to analyse the effects of treatment timing in the surgical management of mandible fractures. A prospective evaluation of 215 continuous patients with a total of 359 mandible fractures was undertaken. Nine outcome variables were analysed in relation to treatment delay by logistic regression modelling: wound dehiscence, hardware exposure, local postoperative infection, malocclusion, trismus, nerve damage, fracture non-union, return to theatre, and radiographic outcome. Nineteen additional variables were included in the analysis to adjust for potential confounding. Delay was measured in days and ranged from 0 to 41 days, with a mean delay of 4.6 days. The incidence of wound dehiscence, hardware exposure, local postoperative infection, trismus, nerve damage, fracture non-union and return to theatre was 6%, 4%, 11%, 8.5%, 47%, 2% and 8%, respectively. Objective malocclusion and poor radiographic outcomes were evident in 13% and 4.5% of cases, respectively. No statistically significant association was found between treatment delay and treatment outcomes. The findings of this study suggest it may be safe to delay the definitive treatment of mandible fractures. Treatment delay may allow for improved resource distribution and prioritization of more time-dependent interventions.